Implementasi Pendekatan Pembelajaran Science Technology Engineering Mathematics Pada Mahasiswa Kimia FMIPA UNIMA - Efrain Sainusa; Sofia S Krisen (Oxygenius Journal Of Chemistry Education, 2021)
The purpose of this study was to determine the percentage of students' critical thinking skills in the chemical reaction in solution topic by using the STEM approach. This research was conducted in the department of chemistry, FMIPA UNIMA in the 2019/2020 academic year. The descriptive qualitative was using for this research with 29 students from first semester of chemical education department as research samples. Data Collection was carried out by 10 posttest essay that include student critical thinking ability. The result of the test show the ability to answer the critical thinking skills are 17,2% for very critical thinking, 44,83% for critical enough ; and 37% for less critical.